Improvement Of Students' Mathematical Problem Solving Skills With The REACT Model - Alyani, Fitri; Nuriadin, Ishaq; Afilah, Nidia (Universitas Ahmad Dahlan, 2020)
The ability to solve mathematical problems is a way of thinking that can be used when trying to solve a problem, it is hoped that students can use it to solve problems in daily life. However, the reality is that students' mathematical problem solving abilities are still low. One effort that can improve students' mathematical problem solving skills is to use the mathematics learning model Relating, Experiencing, Applying, Cooperating, Transferring (REACT). REACT learning model where the REACT model is a contextual learning approach. Contextual learning itself is learning that can motivate and relate problems in everyday life. The purpose of this study is to improve the ability to solve mathematical problems with the REACT model. The research method used in this research is Quasi-Experimental type Pretest-Posttest Control Group Design. The results of this study indicate that students 'mathematical problem-solving abilities with the REACT model are better than students' mathematical problem-solving abilities with conventional models.